Building Legal Identity: MUI South Tapanuli’s Advocacy for the Growth of Islamic Criminal Law in Indonesia - Rita, Rita Defriza; Ade Arga Wahyudi; Ahmad Faisal (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2024)
The discourse on the implementation of Islamic Criminal Law in Indonesia has been a subject of dynamic development, particularly as Islamic values gradually influence national legal frameworks. Against this background, this study aims to explore the perspectives of the Indonesian Ulama Council (MUI) in South Tapanuli regarding the application of Islamic Criminal Law and its relevance to the Islamic Criminal Law academic program. Employing a descriptive qualitative approach, the research captures and analyzes the views of MUI administrators across four regencies and one city in South Tapanuli, using interviews and documentation studies to reveal their perceptions. The findings demonstrate that although Islamic Criminal Law has not yet been fully codified into Indonesia’s positive law, it increasingly serves as a foundational reference in the evolution of the country's criminal legal system. The MUI of South Tapanuli unanimously supports the continuation and strengthening of the Islamic Criminal Law study program, emphasizing its strategic role in bridging Islamic legal principles with societal legal awareness. The study implies that academic institutions and policymakers must collaboratively promote integrative models that harmonize Islamic legal education with national legal development. The novelty of this research lies in its empirical focus on regional ulama perspectives as a grassroots reflection of the socio-legal integration process, offering a rare insight into the localized dynamics of Islamic law adaptation in Indonesia